INCREASING THE STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT THROUGH PLEASE STRATEGY AT THE TENTH GRADE OF SMK NEGERI 1 ULU MOROO IN 2022/2023 - Gulo, Thri Asti; Laoli, Adieli; Daeli, Hidayati; Telaumbanua, Yasminar Amaerita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
through topics provided. Then, students can share their ideas by writing the descriptive text especially describing a personality in correctly. Passing the MCC is a sign of a student's learning progress and is related to their academic achievement, particularly in the English subject. The study aims to improve students' descriptive writing abilities, particularly when it came to using the PLEASE Strategy to describe a personality. The researcher employed Classroom Action Research (CAR) to carry out the study. The eighteen pupils in the tenth grade at SMK Negeri 1 Ulu Moroo were the research subject. In order to gather data, the researcher employed assessment, field notes, and observation as tools. The researcher used essay writing as a tool for evaluation in order to assess the students' writing proficiency. The students' average score in Cycle I was 67.22, and they were unable to meet the MCC. However, the pupils performed well in Cycle II, with an average score of 82.5. The researcher finds that the PLEASE improved the students' writing skills in descriptive text at the tenth grade of SMK Negeri 1 Ulu Moroo in 2022/2023 since the students' marks in Cycle II are higher than those in Cycle I. It can be summed that the PLEASE can be applied in writing process at SMK Negeri 1 Ulu Moroo